Looking at learning communities with the appropriate glasses: hints and ideas from network sciences - Fabio Nascimbeni (Ediciones Universidad de Salamanca, 2013)
<!--[if gte mso 9]> 0 0 1 229 1263 USAL 10 2 1490 14.0 <![endif]--> <!--[if gte mso 9]> Normal 0 21 false false false ES JA X-NONE <![endif]--><!--[if gte mso 9]> <w:LsdException Locked="false" P